PI3-Kinase δγ Catalytic Isoforms Regulate the Th-17 Response in Tuberculosis - Leisching, Gina R. (Frontiers in Immunology, 2019)
IL-17A plays a protective role at the mucosal surface, however when IL-17A signalling becomes dysregulated, a pathological immune response is observed. During the early stages of M. tuberculosis infection, IL-17A contributes to granuloma formation and pathogen containment, however in the progression towards disease this signalling becomes dysregulated and hyper-inflammatory, which drives tissue destruction through enhanced neutrophil recruitment. Many years of research has implicated the PI3-Kinase pathways as one of the most relevant in the pathophysiology of inflammation. Evidence shows that IL-17A secretion and the expansion of the Th17 population is dependant in PI3-kinase signalling, with the p110δ and p110γ isoforms playing a prominent role. The p110γ isoform promotes disease progression through dampening of the Th17 response, preventing pathogen clearance and containment. The p110γ gene, PIK3CG is observed to be downregulated in TB patients during late-stage disease when compared to healthy controls, demonstrating an important modulatory role for this isoform during TB. Conversely, the p110δ isoform induces IL-17A release from pulmonary γδ T-cells, committed Th17 cells and promotes neutrophil recruitment to the lung. Inhibiting this isoform not only suppresses IL-17A secretion from Th17 cells, but it also inhibits cytokine production from multiple T-helper cell types. Since increased IL-17A levels are observed to be localised in the lung compartments (BAL and lymphocytes) in comparison to circulating levels, an inhalable PI3Kδ inhibitor, which is currently utilised for inflammatory airway diseases characterised by IL-17A over-secretion, may be a therapeutic option for TB.